2017
DOI: 10.11113/sh.v9n1-3.1131
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Earnings Management on Dividend Policy in Pakistan

Abstract: The aim of this study was to find out the impact of earnings management on dividend policy of oil and gas companies listed at the Karachi stock exchange. The study uses annual data of oil and gas companies for the period from 2008 to 2015. The dependent and independent variables are dividend policy and earnings management and the three control variables are leverage, return on equity and firm size. Modified cross sectional Jones model (1995) was used for calculating discretionary accruals which has been used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
6
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 6 publications
6
6
1
2
Order By: Relevance
“…Using panel lest square analysis, the study found that there is a negative relationship between DPS and P/E ratio is in both cement and fertilizer sector, which is the same as the result of Aurangzeb and Dilawer (2012) study done in the textile sector. The study also indicated that there is a positive relationship between DPS and P/E ratio in the food and oil and gas sector, which is different from the result of Saleem and Alifiah (2017) study in oil and gas companies. Further, the study concludes that because the nature of the industry differs from each other, the relationship may not be consistent between industries.…”
Section: Literature Reviewcontrasting
confidence: 95%
See 1 more Smart Citation
“…Using panel lest square analysis, the study found that there is a negative relationship between DPS and P/E ratio is in both cement and fertilizer sector, which is the same as the result of Aurangzeb and Dilawer (2012) study done in the textile sector. The study also indicated that there is a positive relationship between DPS and P/E ratio in the food and oil and gas sector, which is different from the result of Saleem and Alifiah (2017) study in oil and gas companies. Further, the study concludes that because the nature of the industry differs from each other, the relationship may not be consistent between industries.…”
Section: Literature Reviewcontrasting
confidence: 95%
“…In the Nigerian context, Ajide and Aderemi (2014) examined the effects of earnings management on dividend policy by using quoted non-financial institutions. Saleem and Alifiah (2017) employed five variables, namely, dividend payout (DPO), discretionary accruals (DA) -calculated using Modified Jones model, size of the firm (SF), return on equity (ROE), and financial leverage (LEV) of the firm in the context of Pakistan. However, the results indicated that earning management expressed a positive relationship with dividend policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…positive, negative and neutral) for the relation between dividends policy and EM. Consistent with Shah et al (2010), Tangestani et al (2016) and Saleem & Alifiah (2017), our results reiterated the absence of a significant relationship between dividend policy and EM in the Kuwaiti market.…”
Section: Correlation Matrixsupporting
confidence: 92%
“…Their results confirmed that in both countries EM has no impact on dividend policy. Saleem & Alifiah (2017) examined the effect of earnings management on dividend policy for (104) Pakistani listed companies' between 2008 and 2015. The study adopted the dividend payout ratio and Dechow et al (1995) and showed no significant relationship.…”
Section: Earnings Management and Dividend Policymentioning
confidence: 99%
“…Plusieurs proxys ont été utilisés pour mesurer la variable à expliquer à l'instar du ratio des dividendes versés, du rendement de dividende, des dividendes par action et des dividendes sur total actif. Cependant, pour notre étude, le choix s'est porté sur le ratio des dividendes versés qui est calculé comme suit [ (Saleem & Alifiah., 2017), (Abreu & Gulamhussen., 2013), Rozeff (1979)] :…”
Section: La Variable Dépendanteunclassified